Cryopreservation techniques and their application in vegetatively propagated crop plants in Finland - Nukari, Anna; Uosukainen, Marjatta; Rokka, Veli-Matti; Antonius, Kristiina; Wang, Qiaochun; Valkonen, Jari P.T (MTT Agrifood Research Finland, 2009)
Cryopreservation protocols have been introduced as techniques for germplasm preservation of vegetatively propagated horticultural and staple food crops. In Finland, cryopreservation has been studied since 1990 s, beginning with cryopreservation of forest tree breeding material and since 2004 on cryopreservation of genetic resources of horticultural plants and potato. Priority was given to cryopreservation of raspberry (Rubus ideaus L.), strawberry (Fragaria x ananassa Duch.) and potato (Solanum tuberosum L.) and the possibility to use cryotherapy in eradication of raspberry bushy dwarf virus (RBDV) from in vitro cultures were studied on raspberry. Modified droplet vitrification cryopreservation protocols were designed for raspberry and strawberry and cryotherapy combined with thermotherapy was proven to be a successful application to eliminate RBDV from infected raspberries. Cryotherapy method can be applied for a large scale elimination of viruses from plant germplasm and from candidate nuclear stock in a certified plant production scheme. Routine use of cryotechniques in germplasm preservation of vegetatively propagated horticultural plants was started. Besides for long term germplasm preservation, cryopreservation techniques can be applied also for maintenance of mother stocks in certified plant production schemes and in commercial plant production. Cryopreservation of potato shoot tips needs additional detailed research to obtain sufficient recovery and regrowth rates.
Keywords: Pu; Ka; cryopreservation; cryotherapy; somatic embryos; raspberries; raspberry bushy dwarf virus; strawberries; potatoes; genetic resources; gene banks; nuclear stock; genetic stability